Uncovering the effect of Moringa oleifera Lam. leaf addition to Fuzhuan Brick Tea on sensory properties, volatile profiles and anti-obesity activity. Issue 5 (14th February 2023) - Li, Xin; Shi, Caihong; Wang, Shuxuan; Wang, Shuang; Wang, Xin; Lü, Xin
Abstract : The Moringa oleifera Lam. leaf addition on FBT for the co-fermentation could increase volatile compounds contents, improve sensory properties and enhance its health benefits. Abstract : As a nutritious plant with valuable potential, the Moringa oleifera Lam. leaf addition to Fuzhuan Brick Tea (FBT) for co-fermentation is an industrial innovation and a new route to make full use of Moringa oleifera Lam. leaves. However, the sensory properties, volatile profiles and anti-obesity activity of Fuzhuan Brick ( Moringa oleifera Lam.) tea (MFBT) are still unknown. The results demonstrated that MFBT has richer and more complex smell and taste, better color and higher overall acceptance scores. In total, 57 volatile flavor compounds, consisting of 3 acids, 16 hydrocarbons, 5 esters, 8 ketones, 13 aldehydes, 6 alcohols and others, were identified using HS-SPME-GC-MS. The characteristic odor components in MFBT were 3-buten-2-one, 4-(2, 6, 6-trimethyl-1-cyclohexen-1-yl)- and 1-cyclohexene-1-carboxaldehyde, 2, 6, 6-trimethyl-, which gave it a floral, woody, sweet, herbal and fruity aroma. 2-Octenal, ( E ) contributed significantly to the aroma of FBT, which could impart fresh, fatty and green aromas. In addition, MFBT could better regulate lipid accumulation, glucose tolerance, insulin tolerance and inflammation response more effectively than FBT. The mechanism is that MFBT could better regulate the dysbiosis of gut microbiota induced by HFFD, mainly increasing the abundance of beneficial bacteria such as SCFA-producing bacteria (Bacteroidetes, Lactobacillaceae, Bacteroidales_S24-7_group and Clostridiaceae_1 ) and decreasing the abundance of harmful bacteria such as pro-inflammatory/obesity and metabolic syndrome-related bacteria ( Proteobacteria, Deferribacteres, Desulfovibrio, Catenibacterium and Helicobacter ), which in turn increased feces short-chain fatty acids and lowered circulating lipopolysaccharides. These results suggested that co-fermentation with Moringa oleifera Lam. leaf could significantly improve the quality and enhance the anti-obesity effect of FBT.